Advances in Catalytic Aerobic Oxidations by Activation of Dioxygen-Monooxygenase Enzymes and Biomimetics - Petsi, Marina; Zografos, Alexandros L. (Synthesis, 2018)
Monooxygenases are not only some of the most versatile machineries in our lives, but also some of the most explored enzymes in modern organic synthesis. They provide knowledge and inspiration on how the most abandoned oxidant, dioxygen, can be activated and utilized to deliver selective oxidations. This review presents an outline in the mechanisms that Nature uses to succeed in these processes and recent indicative examples on how chemists use this knowledge to develop selective oxidation protocols based on dioxygen as the terminal oxidant.1 Introduction2 Monooxygenases2.1 Metal-Based Monooxygenases2.1.1 Cytochromes2.1.2 Copper-Dependent Monooxygenases2.1.3 Heme-Independent Iron Monooxygenases2.1.4 Pterin-Dependent Monooxygenases2.2 Metal-Free Monooxygenases2.2.1 Flavin-Dependent Monooxygenases2.2.2 Systems without Cofactors3 Biomimetic Aerobic Oxidations3.1 Aerobic Oxidations Based on Metal Catalysts3.1.1 Epoxidations and Allylic Oxidations3.1.2 Oxidations of Unactivated Carbon Atoms and Benzylic Oxidations3.1.3 Oxidations of Aryl Groups3.1.4 Heteroatom Oxidations3.2 Aerobic Oxidations Based on Organocatalysts3.2.1 Baeyer–Villiger Oxidations3.2.2 Oxidations of Aryl Groups3.2.3 Heteroatom Oxidations4 Conclusion
Keywords: high-valent metal complexes; flavins; biomimetics; C–H oxidations; sustainable oxidations; green oxidations